High School Dropout in Proximal Context: The Triggering Role of Stressful Life Events. Issue 2 (28th March 2017) - Dupéré, Véronique; Dion, Eric; Leventhal, Tama; Archambault, Isabelle; Crosnoe, Robert; Janosz, Michel
Abstract : Adolescents who drop out of high school experience enduring negative consequences across many domains. Yet, the circumstances triggering their departure are poorly understood. This study examined the precipitating role of recent psychosocial stressors by comparing three groups of Canadian high school students (52% boys; M age  = 16.3 years; N  =   545): recent dropouts, matched at‐risk students who remain in school, and average students. Results indicate that in comparison with the two other groups, dropouts were over three times more likely to have experienced recent acute stressors rated as severe by independent coders. These stressors occurred across a variety of domains. Considering the circumstances in which youth decide to drop out has implications for future research and for policy and practice.